Plasmablastic lymphoma masquerading solitary plasmacytoma in an immunocompetent patient. (21st October 2018) - Diaz, Rodrigo; Amalaseelan, Julan; Imlay-Gillespie, Louise
Abstract : We report a case of a middle-aged woman who initially presented with a painful solitary destructive lesion at fifth lumbar vertebra. The initial diagnosis of plasma cell neoplasm was made based on limited histological information obtained from fragmented tissue sample. Clinicopathological findings were consistent with a solitary plasmacytoma, and she was treated with definitive radiotherapy. A month after completing radiotherapy, she was found to have multiple liver lesions. Subsequent liver biopsy confirmed plasmablastic lymphoma (PBL). She was treated with multiple lines of chemo/immunotherapy regimens with limited or no response. She died of progression of liver lesions causing hepatic failure 16 months post diagnosis. Because of its rarity and heterogeneous presentations, PBL could easily be overlooked clinically and pathologically in immunocompetent patients. Diagnosis of PBL should be considered when there is coexpression of myeloma and lymphoma immune markers.